2008
DOI: 10.1210/jc.2007-2149
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Clinical Experience:Changing Patterns in Diagnosis and Therapy of Acromegaly over Two Decades

Abstract: The primary care doctor plays the major role in diagnosis of acromegaly. The increased use of brain magnetic resonance imaging may contribute to the many incidentally discovered cases and to the shortened time interval to diagnosis. Presumably due to the availability of new medical therapies, the use of radiation therapy has decreased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
83
1
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(94 citation statements)
references
References 36 publications
8
83
1
2
Order By: Relevance
“…The authors of many older series have reported a delay in the diagnosis of 7-10 years after the onset of signs and symptoms. 24 However, in a recent retrospective study Nachtigall et al 50 reported a decrease in this interval to roughly 2-3 years. Given that tumor size has been established as an important predictor of surgical outcome, early recognition and treatment are considered keys to achieving high rates of remission and avoiding long-term comorbidities.…”
mentioning
confidence: 95%
“…The authors of many older series have reported a delay in the diagnosis of 7-10 years after the onset of signs and symptoms. 24 However, in a recent retrospective study Nachtigall et al 50 reported a decrease in this interval to roughly 2-3 years. Given that tumor size has been established as an important predictor of surgical outcome, early recognition and treatment are considered keys to achieving high rates of remission and avoiding long-term comorbidities.…”
mentioning
confidence: 95%
“…Although the disorder has been recognized since antiquity, the pathology of pituitary "prosopectasia" was first described by Andrea Verga in 1864 and the clinical features of acromegaly by Pierre Marie in 1886. Disease pathogenesis involves growth hormone (GH) hypersecretion by tumorous pituitary somatotroph cells, and the diagnosis is invariably preceded by about 10 years of active but unrecognized disease (1)(2)(3). Clinical presentation of acromegaly, in descending frequency as determined in a study of approximately 600 patients, includes acral and facial changes, hyperhidrosis (abnormally increased perspiration), headaches, paresthesia ("pins and needles" tingling sensation), sexual dysfunction, hypertension, goiter, and rarely, visual field defects (4) (see Sidebar 1).…”
mentioning
confidence: 99%
“…However, follow-up suggests that these patients probably did not have acromegaly, First, considering the interval between the onset of manifestations and diagnosis, with the typical phenotype already present (33,34), the absence of this phenotype and of changes in physiognomy after 5 years makes the disease unlikely. Second, spontaneous normalization or absence of an increase in IGF-1 after this period also weakens the diagnosis.…”
Section: Discussionmentioning
confidence: 97%